Transformation Towards Excellence: Narative of Experiences and Coping Strategies Based on Nonformal Educational Values of Islamic Bording School Students with KIP Scholarships - Rimayati, Elfi; Dewi, Widya Novi Angga; Wahidin, Wahidin; Rahmi, Amelia; Ali, Wasir (Journal of Nonformal Education, 2026)
Background — Pesantren as the oldest non-formal educational institution in Indonesia forms graduates with social-spiritual capital, such as khidmah, tawadhu, sincerity, patience, and riyadhoh. KIP-Lecture is present as an instrument of equal distribution of education that opens access for graduates from economically vulnerable families, including Islamic boarding schools, to formal higher education. However, the transition from pesantren to tertiary education presents complex academic, social, psychological, and digital challenges. Research Urgency — Empirical studies on the experiences of Islamic boarding school graduates who received KIP-Lecture in navigating the transition to non-formal education are still limited, although it is important to design scholarship support that is sensitive to the educational background and adaptation needs of students. Research Objectives — This study aims to describe the transition experience of Islamic boarding school graduates who receive KIP-Lecture and map the transformation of pesantren values, such as khidmah, tawadhu, sincerity, and riyadhoh, into a productive coping strategy. Research Method — The research used a phenomenological-narrative qualitative approach with 10 active KIP-Lecture recipients who lived in Islamic boarding schools and were selected purposively. Data was collected through in-depth interviews, personal documents, observations, and academic records. Analysis is carried out through transcription, horizontalization, theme grouping, textural description, restorying, and interpretation of meaning. Research Findings — Findings show that pesantren graduates experience value negotiations between pesantren culture and higher education demands, such as academic activeness, critical thinking, innovation, and digital literacy. This transition not only raises identity tensions, but also encourages a reinterpretation: solemnity becomes an academic mandate, tawadhu becomes readiness to learn, and sincerity becomes active acceptance accompanied by effort. The coping strategies formed are integrative, including problem-focused, emotion-focused, meaning-focused, and religious coping. Islamic boarding school spiritual practices, such as night prayers, dhikr, tawakkal, and riyadhoh, function as emotional regulation, strengthening thinking, and a source of academic meaning. Research Conclusion — The social-spiritual capital of pesantren is an adaptive resource for pesantren graduates in formal higher education, so that the relationship between non-formal and formal education needs to be understood as a complementary continuum. Research Novelty/Contribution — This research offers an integrative coping model based on socio-spiritual capital of pesantren to support KIP-Lecture policies, student transition assistance, and strengthening non-formal education studies across levels.